2016
DOI: 10.1097/dcc.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Registered Nurses’ Decision to Activate an Adult Rapid Response Team in a Community Hospital

Abstract: Organizations should examine RRT activation delays particularly in the area of calls to covering physicians prior to RRT activations. Differences between specialty groups highlight the need for education across specialties on the recognition of the acutely deteriorating patient. The findings indicate that the inexperienced nurse requires support from experienced colleagues and temporary adjustments to workload during situations of acute deterioration of a patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…This was achieved by making the most of the numerical scoring classification. In doing so, the nurses were adhering to local policies; whilst on the other hand relinquishing their immediate responsibility to another healthcare professional, (Kyriacos 2011, Martin 2012, and Jackson & Penprase 2016 Remarkably, none of n=10 participants offered any explanation for the elevation of the physiological parameters. These parameters were essentially used as a landmark to connect the numerical score to the specific vital signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was achieved by making the most of the numerical scoring classification. In doing so, the nurses were adhering to local policies; whilst on the other hand relinquishing their immediate responsibility to another healthcare professional, (Kyriacos 2011, Martin 2012, and Jackson & Penprase 2016 Remarkably, none of n=10 participants offered any explanation for the elevation of the physiological parameters. These parameters were essentially used as a landmark to connect the numerical score to the specific vital signs.…”
Section: Discussionmentioning
confidence: 99%
“…Utilising, the Modified Early Warning Score as a tool to escalate concerns commonly referred to as the acronym (MEWS). The correct utility of the T&T system plus a basic understanding and interpretation of the physiological changes is needed to activate this process, (Considine et al 2015, Fasolino & Verdin 2015Smith & Aitken 2015, Jackson & Penprase 2016.…”
Section: Initiatives To Improve the Care Of The Deteriorating Patientmentioning
confidence: 99%
“…These reviews could consider standardising decision-making processes including the transfer of consumers post an APD event, particularly in terms of parameter-setting surrounding medical clearance and level of medical deterioration that can be managed in a mental health unit. While nurses in our study felt that there were unrealistic expectations about the level of medical morbidity they were expected to cope with, it may be that a more constructive response might be to improve their skills and confidence to deal with these complexities rather than relying on protocols of ev- Jackson, Penprase, & Grobbel, 2016;Reardon, Fernando, Murphy, Rosenberg, & Kyeremanteng, 2018;Wilson et al, 2017;Yun et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…7 To improve communication, Bailey and colleagues 8 added an EWS alert to the medical-surgical charge nurse's pager but could not explain a lack of improvement in patients' outcomes, suggesting that a more integrated approach to identify interventions is needed. Jackson and others 9 reported a strong negative correlation between medical-surgical nurses' years of experience and reluctance to activate an RRT call. They concluded that "collaborative support from seasoned colleagues" targeting inexperienced medical-surgical nurses could improve outcomes of patients whose condition is deteriorating.…”
Section: Introductionmentioning
confidence: 97%
“…They concluded that "collaborative support from seasoned colleagues" targeting inexperienced medical-surgical nurses could improve outcomes of patients whose condition is deteriorating. 9 Experienced ICU nurses serving on RRTs are trained to recognize and intervene in situations of clinical deterioration. We hypothesized that an EWS communication bundle including an experienced ICU nurse would decrease transfers, RRT calls, and morbidity of medical-surgical patients transferred to the ICU.…”
Section: Introductionmentioning
confidence: 99%